Examination and Confiscation of Notarial Deeds for The Purpose of Criminal Law Enforcement without Approval from The Notary Honorary Council - Moh. Roziq Saifulloh (Jurnal Penelitian Hukum De Jure, 2022)
The Notary’s right of refusal through the approval of the Notary Honorary Council (NHC) hinders the practice of criminal law enforcement because it is absolute and there is no further (final) legal remedy, even though a similar policy (beleid) has been revoked by the Constitutional Court. In practice, the notary cannot be examined by investigators, public prosecutors, or judges, unless they have previously obtained NHC approval, as regulated in Article 66 paragraph (1) of Law Number 30 of 2004 as amended by Law Number 2 of 2014 (Notary Position Law). Even if Notary Honorary Council refuses, then there will only be further legal remedies through a lawsuit by the State Administrative Court. In fact, the provisions regarding the Notary’s right of refusal should be ‘determination’ by court decisions (vonnis) as regulated in Article 170 of the Criminal Code, and not ‘administrative determination’ (beschikking) through NHC approval based on the delegation of supervisory authority from state institutions. This paper concludes that every law enforcer in criminal cases (police, prosecutors, and judges) can examine a Notary with the condition of special permission from the Head of the local District Court, approval of direct interested parties, or NHC approval as stipulated in Article 43 of the Criminal Code in conjunction with Article 66 paragraph (1) of the Notary Position Law. This paper is normative research with a statutory approach, conceptual approach, and case approach.